Green intelligent building design based on integrated photovoltaic/thermal building - Wang, Tianchi (International Journal of Renewable Energy Development, 2025)
With the increasingly prominent contradiction between energy consumption and environmental governance, the integrated photovoltaic/thermal building system has broad development prospects in building energy conservation. However, the improper placement of photovoltaic solar thermal collectors results in the inability of solar energy systems to maximize energy conversion. In order to combine photoelectric photothermal technology with architectural design, realize the efficient conversion and utilization of solar energy, reduce the dependence on traditional energy sources, and reduce building energy consumption, research based on the comprehensive utilization technology of solar photovoltaic photothermal building, designed an integrated photovoltaic photothermal building system, and optimized the system for different light resources and environmental conditions of solar photovoltaic photothermal collectors. The system achieved zero energy operation when the total energy consumption in winter was 798.92kW·h. The cumulative power supply and heat generation of the integrated photovoltaic/thermal building system throughout the winter were 214.63kW·h and 79.68kW·h. This study uses solar photovoltaic solar thermal collectors to replace roof coverings or insulation layers, which declines the impact of solar energy on buildings, and avoids duplicate investment and cuts cost. This study can improve power generation efficiency, meet heating needs, enhance resource utilization efficiency, reduce environmental pollution, and promote the sustainable development of the construction industry